Cognitive development in school performance in high school students - Chávez-Mendoza, María Virginia; Alcívar-Cedeño, Monserrate Dalila del Rocío (International research journal of management, IT and social sciences, 2022)
The objective of this research is to determine the cognitive development in the school performance of the students of the upper basic of the fiscal educational institution "Santa Rita", of the Chone canton in the period 2021-2022. The applied methodology had an exploratory and descriptive quantitative-qualitative approach, taking the position of several authors and the opinion of directors and teachers of higher basic education; since they are the ones who guided the teaching-learning process of the students under their charge through various disciplines. When investigating teachers based on the survey carried out, it is evident that most of the respondents have followed the regulations and guidelines issued by the Ministry of Education through the districts with teaching through interdisciplinary projects and the implementation of a curriculum prioritized by the crisis experienced in the pandemic by Covid 19. The result was that teachers assumed the responsibility of bringing knowledge, but also becoming aware of the circumstances and motivation was permanently delivered so that students will take the right direction, being mostly the architects of their learning such as self-discipline, responsibility, and care.